Socioeconomic inequalities in the non-fatal and fatal burden of disease: findings from Scottish Burden of Disease (SBoD) 2016 Scottish Burden of Disease Project Team - Grant, Ian; Wyper, Grant; Mesalles-Naranjo, Oscar; Kavanagh, Jade; Tod, Elaine; Stockton, Diane (International Journal of Population Data Science, 2018)
Background SBOD2015 was the first endeavour to produce burden of disease estimates in Scotland using linkage of routine health records. In 2017, the study highlighted disparities in burden due to morbidity and mortality with respect to age and gender for 132 conditions, diseases and injuries. Objectives The aim of SBOD2016 is to report on socioeconomic inequalities to provide further evidence to support preventable public health. Methods Morbidity estimates were estimated using an extensive range of administrative datasets to provide a transparent and systematic approach to describe non-fatal population health loss. Combining these estimates with the Global Burden of Disease 2016 study’s relative assessment of severity and disability for each condition, we were able to calculate the Years Lived with Disability (YLD). Death registrations were used alongside life expectancy data to calculate the Years of Life Lost to premature mortality (YLL) as a measure of fatal burden. Findings Preliminary findings show a three-fold increase in the burden of disease between individuals living in the most deprived areas compared to the least deprived areas. The profile of diseases contributing the largest burden also varies between the most and least deprived areas. Conclusions By combining information on fatal burden with the burden of living in less than ideal health (non-fatal burden), planners and policymakers have a better idea of the contribution that different diseases, conditions and injuries make to the total burden of disease and how this varies by levels of deprivation. This in turn provides information to support decisions about where prevention and service activity should be focused. It also provides a way of looking at the proportion of the burden that can be explained by a range of exposures in the population such as poverty or smoking.